The complex plant commnities of the campo rupestre habitats untalgled by trait-based approach - Dario Caminha Paiva (2020)
Old, climatic buffered and infertile landscapes (OCBILs) are remarkably species-diverse habitats, and the structuring of their ecological communities is scarcely known. The main objective of this study was to understand how edaphic filters drive the functional structure of plant community in an ancient and nutrient-impoverished habitat. We carried out a functional screening across four types of campo rupestre habitats with different edaphic conditions. We investigated trait-soil relationships for ironstone and quartzitic substrate to obtain the optimal trait values of each condition. Also, we built unipartite networks to explore trait-trait relationships aiming to assess functional coordination among organs. Lastly, we run Blomberg’s K to test trait phylogenetic signal. The greater the soil acidity and less potential to soil water retention, the greater were the proportion of smaller leaves, tissue dry mass and density resulting in more resource conservative plant species and communities. Trait functions were tightly correlated among organs both at the plot and individual level, indicating a trend of morphological integration. Architectural traits were central in coordination, suggesting their key role at the integration of sap transport, mechanical support, and leaf display. Most of traits had a low phylogenetic signal and the statistically significant traits were normally associated with mechanical support/ sap transport. We conclude that the trait adjustments in response to soil parameters are an important mechanism to the coexistence of a high number of species in campo rupestre landscape.